Sleep and Learning: A Systematic Review - Gutiérrez Pérez, Martha Lucía; Lugo Machado, Juan Antonio; Lozano Lavado, Valeria; Navarro Pimiento, Diana Camila (International Archives of Otorhinolaryngology, 2024)
Introduction Sleep deprivation has a great impact on the learning process in physicians in training. Therefore, inquiring on this phenomenon in the most recent investigations will facilitate the provision of evidence on the influence regarding the absence of sleep on the learning process in health personnel.Objectives The aim of this systematic review is to review, analyze and discuss the current literature that shows the impact of sleep on the learning process on doctors in training.Data Synthesis A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A search of the existing literature between the years of 2000 and 2022 was performed in the PubMed and Elsevier databases, taking into account the inclusion criteria of articles in English or Spanish and the established timeframe. As a result, 128 articles distributed in the databases were obtained and 23 articles that met the inclusion criteria were selected.Conclusion Sleep is a fundamental factor for the consolidation, processing and functioning of memory and learning. Health professionals are a population at risk of sleep deprivation, thus it is important to take into account the effects it has on patients and health personnel.
Keywords: sleep; learning; internship and residency; systematic review